2006
DOI: 10.1111/j.0008-3658.2006.00138.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of residential exposure to steel mills and coking works on birth weight and preterm births among residents of Sydney, Nova Scotia

Abstract: The Sydney Tar Ponds in Sydney, Nova Scotia, Canada, have been referred to as the most contaminated industrial site in the country. Area residents, aware of the contamination for close to 25 years, are very concerned about their health: past, present and future. In particular, they are concerned about cancer; this is followed closely by reproductive health concerns. The objective of this study was to assess the prevalence and determinants of birth weight and preterm birth among residents living in proximity to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2007
2007
2011
2011

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 57 publications
1
4
0
Order By: Relevance
“…The plots also show that there is no clear relationship between distance and risk. This result is consistent with the results of two of the studies conducted in this area using primary data [ 1 , 3 ]. They both concluded that a causal association between preterm births and maternal/residential proximity to the Tar Ponds could not be inferred from the statistical analysis.…”
Section: Resultssupporting
confidence: 91%
See 1 more Smart Citation
“…The plots also show that there is no clear relationship between distance and risk. This result is consistent with the results of two of the studies conducted in this area using primary data [ 1 , 3 ]. They both concluded that a causal association between preterm births and maternal/residential proximity to the Tar Ponds could not be inferred from the statistical analysis.…”
Section: Resultssupporting
confidence: 91%
“…This concern has led to an increased demand for public health authorities and researchers to investigate potential clustering of diseases around putative sources of hazards [ 1 - 10 ]. Evidence of significant association between maternal proximity to hazardous waste sites and risk of low birth-weight and congenital anomalies has been reported in some studies [ 4 - 12 ], but other studies have reported otherwise [ 1 , 3 , 6 , 13 - 15 ]. Some studies have also shown that women exposed to PCB are at increased risk of giving birth to infants with low birth weight [ 16 , 17 ].…”
Section: Introductionmentioning
confidence: 99%
“…10,11 In studies after the industrial complex closed, for the period 1988-1998 a 25% increase in rate ratio for all major congenital anomalies was observed in Sydney relative to Nova Scotia, 12 and a small increase in low-birth-weight and preterm births have been reported for an area most impacted from the industrial emissions relative to other areas in Sydney. 13 In addition, adolescents living near the tar ponds have health-related concerns about themselves and their families. 14 This study contributes to understanding the role of environmental pollution in the health effects observed in Sydney by evaluating the spatial impact from the industrial emissions through analysis of soil contamination.…”
Section: Fig 1 Area Map Showing Sydney and North Sydney (Figure Ismentioning
confidence: 99%
“…Examples include proximity to toxic releases from industries (Burra et al, 2006;Choi et al, 2006), as well as proximity to non-point sources of aqueous nitrates, petrochemicals (Yu et al, 2006) and other environmental contaminants (Wickre et al, 2004). Proximity measures prove especially valuable when estimating exposures that occurred many years ago, and when present-day biomarkers are not appropriate measures of past exposures.…”
Section: Introductionmentioning
confidence: 99%